Using Mobile Language Learning Technology to Promote Intercultural Awareness: Insights From an Extensive Listening Class - Ratna Andhika Mahaputri; Hendriwanto Hendriwanto; Wendi Kusriandi (Sakura Digital Nusantara, 2026)
Purpose: This study reports on the intervention of technology-enhanced language learning in an extensive listening class to promote intercultural awareness. Methods: The nature of the present study was exploratory as the recruited students were engaged in virtual language learning tasks through different online platforms, such as zoom meetings, podcasts, Padlet, and other online listening resources (ESL Fast, BBC Learning English, voice tube, and news in level). A phenomenological case study was adopted to investigate the intervention of technology-enhanced language learning to promote intercultural awareness perceived through the participants’ perspective. Data were garnered through analysis with interpretative phenomenological analysis (IPA) and critical discourse analysis (CDA) from questionnaires and interviews. Findings: The learners’ intercultural awareness was perceived to enhance during the experiences of extensive listening mediated by technology. Generally, they respond positively to intercultural incidents within various topics of intercultural listening. Research Implications: This study contributes to the research on technology-enhanced intercultural learning with extensive listening activity in EFL teaching. In this sense, the students teachers’ perceptions of intercultural awareness development during technology-mediated extensive listening, rather than providing intervention effectiveness. Originality: The present study investigates the intervention of language learning technology to promote intercultural awareness in EL class. Furthermore, the language learners’ responses to various online listening platforms concerning intercultural topics are also discussed.